Assessment of the inhibitory effect of two local plants on the emergence of four weeds and identification of their secondary metabolites: Case of Parkia biglobosa (Jacq.) R.Br.ex G.Don. and Tephrosia purpurea (L.) Pers. (International Journal of Agricultural Research, Innovation and Technology, 2023)
In Burkina Faso, Senna occidentalis, Ipomoea eriocarpa, Pupalia lappacea and Triumfetta cordifolia are frequent weeds in the maize crop. This work evaluated the inhibitory effect of Parkia biglobosa pods and Tephrosia purpurea leaves and identifies their chemical compounds. Biological and chemical approaches were used to identify the weeds. The inhibitory effect of powders was evaluated on weed germination and growth.  Experimental results showed that powders reduced both germination (p